Best Practice Personal Hygiene Orang Tua Balita Stunting : Studi Kasus Di Desa Batulappa dan Desa Kassa - Hasni, Nur; Amir, Rahmi; Nurlinda, Nurlinda (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Stunting is still a nutritional problem experienced by toddlers in the world, including in Indonesia. This study aims to determine the application of best practice personal hygiene for parents of stunted toddlers in rural areas. The type of research used is descriptive qualitative method research prospective case study. The informants in this study were 17 informants in Batulappa Village and Kassa Village. Data collection techniques in this study were interviews and observations and data analysis techniques used in this study were triangulation techniques. The technique is a multi-method approach that researchers take when collecting and analyzing data. The results showed that the majority of informants in Batulappa Village and Kassa Village implemented clean delivery practices, but awareness of the importance of using clean water and washing hands with soap was still low. Although some used healthy latrines, none conducted mosquito larvae eradication at home, highlighting the importance of raising awareness of environmental health. Conclusion Hygiene practices such as handwashing and using clean water and healthy latrines still need to be improved in Batulappa Village to reduce the risk of stunting in under-fives, while education on mosquito larvae eradication is also important to prevent the transmission of diseases that contribute to stunting. Suggestion: Improving education, awareness and sanitation infrastructure as well as mosquito vector eradication education programs can help reduce the risk of stunting in Batulappa Village. Keywords: Best practice personal hygiene;  stunting; rural areas